Identification of microplastics content in milkfish (Chanos chanos), water and sediment in ponds in Muncung Village, Kronjo District - Muhammad Figo Azuri; Dodi Hermawan; Desy Aryani (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Plastic is a product that is currently popular among people, but over time plastic can be dangerous for the environment. Plastic can degrade into smaller particles known as microplastics. Microplastics in waters can harm aquatic biota such as fish. The size of microplastics is so small that it easily enters the fish's body, settles in the digestive tract and affects the fish's life cycle. Apart from biota, microplastics also pollute water and sediment. The aim of this research is to determine the abundance of microplastics and identify the characteristics of microplastics in milkfish in ponds in Muncung Village. The method used is take fish from ponds at 6 stations along with water and sediment. The fish were dissected and the digestive organs and flesh were removed, while the water and sediment were treated with NaCl. The microplastics found will be tested by FTIR to determine the polymer. The results of the observations showed that there were 3 types of microplastics, namely fragments, fibers and films. The highest abundance in organs was in the intestine, while microplastics were also found in water and sediment. FTIR test results show 6 plastic polymers in milkfish, namely ABS, latex, PVC, PP, EVA and nitrile. Keywords: Microplastics, milkfish, FTIR, Muncung Village